ALGORITMA ESTIMASI PENGGUNAAN DAYA LISTRIK DC PADA LISTRIK PORTABEL - Mochammad Dava Rizqie; Akhmad Zainuri; Muhammad Fauzan Edy Purnomo (Jurnal Mahasiswa TEUB, 2022)
This study aims to ensure the estimation of power usage time in portable power supplies. The main component of this system is a portable power supply which contains a battery as a power supply, a current shunt as a current sensor, and Arduino as a microcontroller. The portable power supply will store energy from the solar cell through the solar cell power supply. When using a portable power supply, the parameter to consider is the output current because it will be an assessment of power usage in units of time, because not everyone knows the battery voltage limit. The current value is obtained from the Current shunt current sensor. The conversion of the current value into an estimate of time is by calculating the power equation. Current Shunt sensor is a sensor that has positive and negative poles with the ability to read currents up to 100A 60 mV. This shunt current sensor requires a signal conditioning circuit that is used as an amplifier circuit on the sensor. This circuit contains IC AD620 as an op-amp which has advantages at high frequencies and has a high level of precision. The time value will be displayed on the LCD 16x2 contained in the portable power supply. The load contained in this experiment is a 25W DC load and 100W AC through an inverter.Keywords: Estimated power usage, current sensor, power supply, battery